Understanding the mechanical reinforcement of uniformly dispersed multiwalled carbon nanotubes in alumino-borosilicate glass ceramic - Mukhopadhyay, A; Chu, B; Green, M; Todd, R (2010)
The improvement of mechanical properties of carbon nanotube-reinforced polycrystalline ceramic or glass matrix composites was limited in earlier studies by the difficulties in producing a good dispersion of carbon nanotubes. Additionally, a proper understanding of the reinforcing mechanisms, if any, affecting the mechanical properties of ceramics containing carbon nanotubes is still lacking. We report here the effects of a good dispersion of as much as 10 wt.% multiwalled carbon nanotubes (MWCNTs) on the mechanical properties of dense alumino-borosilicate glass ceramics (ABS) prepared by an ultrasonication-assisted sol-gel technique followed by hot pressing (950 °C; 2 h; Ar atmosphere). The fracture toughness and flexural strength of the nanocomposites increased with increasing MWCNT content up to 10 wt.%. The ABS-10 wt.% MWCNT nanocomposite possessed nearly double the strength of the unreinforced ABS, accompanied by ∼150% improvement in fracture toughness. However, a further increase in MWCNT content to 15 wt.% resulted in a modest deterioration of the mechanical properties due to agglomeration of the MWCNTs. The carbon nanotubes have been observed to bridge crack openings of the order of ∼100 nm and the experimental evidence, along with theoretical analysis, showed that crack bridging provided the major contribution towards the improvement in fracture toughness. Debonding between the MWCNTs and the matrix appeared to occur in the matrix, away from the actual interface. However, the absence of significant pull-out of broken sections of the MWCNTs during fracture, due to failure of the bridging CNTs being predominantly at the crack plane, indicates that further toughening may be available if this mechanism can be activated. © 2010 Acta Materialia Inc.